Gender in infrastructure lessons from Central and West Asia. ([Manila] Asian Development Bank, 2019)
Infrastructure projects may reinforce gender inequality if womens needs are not recognized in project design. The Asian Development Bank actively promotes gender mainstreaming in its infrastructure projects in Central and West Asia. In the publication, project results illustrate how gender inclusion contributes to meeting the needs of all beneficiaries and creating opportunities for regional economic growth.
Keywords: Public administration; Gender equality -- Infrastructure -- Asia; Electronic books